Possibility of using computational fluid dynamics (CFD) for urban canyon studies in tropical climate - Then, Jit Hiung; Ahmad, Mohd. Hamdan (Fakulti Alam Bina, UTM, 2006)
This paper gives an overview of research methods for urban street canyon studies, from the commonly used field experiments and scaled models methods to numerical simulation models. Review of field experiments and scaled models showed identical weaknesses in dealing with urban canyon studies i.e. cost, time consuming and data or information obtained is rather limited or specific and often do not yield all of the designers’ requirement. Numerical simulation on the other hand is an effective tool of understanding the complicated processes within the urban canopy layer. Numerical simulations using Computational Fluid Dynamics (CFD) is reviewed. CFD is well-known for its ability for evaluating either internal or external air flow and pollutant dispersion. In this paper instead, the possibility of using this model for urban canyon thermal environment studies in tropical climate is emphasized.